Correlation of platelet indices with TIMI frame count in patients undergoing primary PCI due to ST-segment elevation myocardial infarction - Salehi, Ayoub; Namazi, Mohammad Hasan; Safi, Morteza; Vakili, Hossein; Saadat, Habibollah; Alipour Parsa, Saeed; Akbarzadeh, Mohammad Ali; Moshtaghi, Ameneh; Khaheshi, Isa (International Journal of Cardiovascular Practice, 2019)
Introduction: Given the fundamental role of platelet indices in the development of atherosclerotic plaque, these indices may play a predictive role for the occurrence of disturbed coronary reperfusion. The present study evaluated the relationship between platelet indices and coronary reperfusion status based on TIMI frame count.Methods: This cross-sectional study was conducted on 98 consecutive patients with STEMI who were candidate for primary PCI at Modarres Hospital in Tehran between January 2016 and January 2018. Venous samples were extracted from all patients before primary PCI. To assess the condition of coronary reperfusion after primary PCI, TIMI frame count related to culprit artery in acute myocardial infarction was determined.Results: The TIMI frame count was positively associated with platelet count (r = 0.320, p = 0.001) and more strongly with platelet to lymphocyte ratio (r = 0.375, p < 0.001), but not with other platelet indices such as PDW, MPV, or PLCR. According to the ROC curve analysis, platelet to lymphocyte ratio was introduced as a valuable parameter for differentiating complete from disturbed reperfusion (AUC = 0.735, 95%CI: 0.613 ? 0.858, P = 0.001). The best cutoff value for platelet to lymphocyte ratio in predicting disturbed reperfusion was 146.5 yielding a sensitivity of 81.8% and a specificity of 60.5%. However, other platelet indices could not present this predictive role.        Conclusion: From different platelet indices, the platelet to lymphocyte ratio with predictive accuracy and sensitivity predict coronary perfusion impairment based on the increase in TIMI frame count.